Educational software for stress analysis of idealized multi-spar aircraft wing - Afiq Safwan, Ahmad Afandi; Jaffar Syed, Mohamed Ali (2021)
The cross-section of a wing carries stresses such as bending, torsional and shear. The analysis in aircraft structure courses is done by assuming bending stress is only assumed to affect boom areas while shear stress only affects the skins of the cross-section. A MATLAB software has been developed with the purpose to compute the stresses and the shear centre of the cross-section. The software includes choices for tapered or non-tapered wingspan, boxed or curved leading edge, and with or without extra booms. The software is validated with some literature problems, the comparison shows low percentage difference between the two.